The Portuguese state of the art on osteoporosis and fracture risk: an update on the treatment options - Ramalho, Diogo; Rocha, Gustavo Melo; Oliveira, Maria João (Aktuelle Rheumatologie, 2023)
Osteoporosis and fragility fractures are serious public health problems, which greatly impact individual health and the economy of other health services. Pharmacological treatment is still one of the main elements of clinical intervention, combined with non-pharmacological measures, in preventing the occurrence of fragility fractures. The emergence of promising new pharmacological options in the treatment of osteoporosis seems to renew expectations in the prevention of complications and a subsequent reduction in morbidity and mortality, including symptomatic treatment, improved physical function and a better quality of life. This review aims to provide updated information on the pharmacological treatment of osteoporosis in the adult population. A comprehensive PubMed search was performed to review the current evidence on osteoporosis treatment. Of the 378 articles identified from the initial queries, the final review included 80 articles. Currently, the following pharmacological options are available: antiresorptive (bisphosphonates, denosumab, postmenopausal hormone replacement therapy and selective oestrogen receptor modulators), bone-forming agents (essentially, teriparatide and abaloparatide) and the new dual-action therapy (romosozumab), recently approved by the US Food and Drug Administration and the European Medicines Agency, but which is not yet an option in Portugal. Therapeutic selection is essentially based on assessment of cost-effectiveness, since current evidence does not suggest any differences between the distinctive classes in reducing the risk of fractures, but this analysis is limited by the scarcity of comparative intraclass studies. Notwithstanding, romosozumab, as a dual effect therapy, is promising in resolving the physiological limitations resulting from the merely unilateral action of antiresorptive agents and bone-forming agents in the inseparable relationship between bone formation and resorption. However, its cardiovascular safety raises some concerns, and this topic is still being debated. The underdiagnosis and the undertreatment of osteoporosis remain one of the greatest challenges of the 21st century. Over the years, new drugs have appeared that have tried to address these problems with a direct impact on the health of populations, but a long way remains to be come in optimising their effectiveness, safety and tolerability.
Keywords: osteoporosis; bone density conservation agents; denosumab; romosozumab; abaloparatide